Clinical researchB-type natriuretic peptide level in adult patients after successful repair of coarctation of the aorta - Trojnarska, Olga; Bręborowicz, Piotr; Gwizdała, Adrian; Pyda, Małgorzata; Oko-Sarnowska, Zofia; Szyszka, Andrzej; Grajek, Stefan (Archives of Medical Science, 2008)
Introduction: The aim of the study was to evaluate BNP in adults after successful surgery of CoAo. Material and methods: Seventy-four patients after surgery of CoAo entered the study group aged 31.2±9.8 and operated at age 10.4±6.8. The control group consisted of 30 healthy volunteers (18 males) aged 32.2±6.6. 2D and Doppler echocardiography was performed. Patients were divided into two groups: with or without DAo restenosis. All patients underwent an exercise treadmill test. Patients were enrolled in the study if they were found to have untreated HT or if a two-week cessation of hypotensive therapy was possible. In all cases BNP level was measured. Results: 32 patients showed normal BP while 10 had exercise-induced HT. The remaining patients had chronic HT. The maximal systolic gradient in DAo was comparable in all groups. In 33 patients residual DAo stenosis was noted (DAo+) 36.6±9.8 mm Hg, and in another 41 it was not (DAo–) 15.9±5.1. The maximal transvalvular aortic pressure gradient was 11.7±6.2 mm Hg. BNP in the study group was higher than among controls, though it was higher in the DAo+ subgroup than in the DAo– subgroup. BNP level also correlated with patients’ age at the time of operation (R=0.275, P=0.02), and with transaortic gradient (R=0.233, P=0.04). Conclusions: BNP in adults after CoAo repair is significantly elevated, which may be due to the pressure load of LV.